Preparation process of plain conductive cloth single-sided adhesive tape
The conductive fabric tape manufacturing process addresses adhesive weaknesses by using gradient-oxidized starch adhesives and controlled drying, achieving enhanced strength and durability for precision electronics and packaging applications.
Patent Information
- Application Number
- CN202510598071.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-09
- Publication Date
- 2025-07-15
AI Technical Summary
Existing starch-based adhesives are insufficient in humid environments, poor water resistance, and prone to mildew, resulting in limited applications in areas such as precision electronic packaging and weather-resistant packaging.
Gradient oxidation crosslink modification technology is used to construct a three-dimensional network structure adhesive, combining conductive carbon black and silane coupling agent, optimize the conductive-adhesive interface, activate the surface of the conductive cloth through low-temperature plasma treatment, and form a stable conductive layer through segmented drying and high-temperature curing.
It improves the water resistance and mechanical strength of the adhesive, reduces the resistivity, ensures the long-term reliability and environmental protection of the tape, and reduces electronic waste pollution.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of chemical technology, and particularly relates to a preparation process of a plain conductive cloth single-sided tape. Background Art
[0002] Conductive cloth tape is a functional tape made by compounding an adhesive on a conductive cloth substrate. Its core characteristic is the combination of the electromagnetic shielding performance of the conductive cloth and the bonding function of the adhesive layer. This product is widely used in the fields of electronics and electrical appliances such as computers, mobile phones, and cables. By forming a conductive interface in the high-frequency signal transmission path, it effectively shields or isolates electromagnetic wave and radio wave interference, ensuring the signal stability of the device. Compared with traditional petroleum-based adhesives, starch-based adhesives have become a highly potential environmentally friendly alternative material due to their wide raw material sources, low cost, renewable, and biodegradable characteristics. However, natural starch molecular chains have high rigidity and strong hydrophilicity, resulting in significant defects in starch adhesives prepared by traditional processes: insufficient bonding strength, poor water resistance (wet state peel strength drops > 30%), easy to mildew during storage, and easy to debond and fail in humid environments or low-temperature cold storages, severely restricting their applications in fields such as precision electronic packaging and weather-resistant packaging. To address this technical bottleneck, the academic community has carried out structural reorganization of starch through chemical modification means such as oxidation, crosslinking, and graft copolymerization, as well as new methods such as biomass polymerization, nanocomposite, and irradiation treatment, significantly improving its bonding strength (up to more than 2.5 MPa), water resistance (water absorption rate < 15%), and thermal stability, enabling it to meet the process requirements of high-end scenarios such as food and pharmaceutical packaging, biological hemostatic materials, and special paper bonding.
[0003] In view of the above problems, the present invention proposes a preparation process of a plain conductive cloth single-sided tape, using corn starch as the main raw material, constructing a three-dimensional network structure adhesive through gradient oxidation crosslinking modification technology, and optimizing the conductive-bonding interface by coordinating conductive carbon black and silane coupling agent KH-550, and finally preparing the tape by combining with the conductive cloth, reducing carbon emissions and reducing electronic waste pollution. Summary of the Invention
[0004] The purpose of the present invention is to address the above problems existing in the prior art and propose a preparation process of a plain conductive cloth single-sided tape.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A preparation process of a plain conductive cloth single-sided tape, comprising:
[0007] S1. Prepare a conductive adhesive. Prepare a corn crosslinked oxidized starch adhesive according to the steps, add conductive carbon black, sodium lignosulfonate, and silane coupling agent KH-550, and stir for 30 - 60 minutes to form a conductive adhesive;
[0008] S2. Pretreatment of plain conductive fabric: low-temperature plasma treatment of plain conductive fabric, power of 50-100W, treatment time of 2-5min, introduction of argon or oxygen mixed gas, ratio of 4:1;
[0009] S3, coating process, use a scraper coater or a roller coater to evenly coat the conductive adhesive on one side of the conductive fabric, and control the wet film thickness to 50-100 μm;
[0010] S4, staged drying, the first stage is drying at 40°C and 50% humidity for 5 minutes, the second stage is drying at 60°C and 30% humidity for 10 minutes to accelerate water evaporation;
[0011] S5, curing and molding, curing at 100-120°C for 20-30 minutes to completely cross-link the adhesive and form a stable conductive layer;
[0012] S6, pressing and slitting, using the pressing roller to ensure that the adhesive layer and the substrate are in close contact, and then slitting into rolls or sheets according to production requirements.
[0013] In terms of materials, a balance between environmentally friendly substrate and conductive performance is achieved through the combination of corn cross-linked oxidized starch adhesive and conductive carbon black. Adhesion is enhanced through pretreatment, and the surface of the conductive cloth is activated using low-temperature plasma treatment to improve the wettability of the adhesive and reduce the risk of delamination. In the subsequent segmented drying process, temperature and humidity are controlled in stages to avoid cracking of the adhesive layer, ensure drying uniformity, shorten process time, and promote complete cross-linking through high-temperature curing to form a stable conductive network and ensure long-term reliability.
[0014] Preferably, in step S1, before stirring, the conductive carbon black is mixed with sodium lignin sulfonate, KH-550 and a small amount of ethanol, and ultrasonically treated for 30 minutes;
[0015] Among them, the ultrasonic frequency is 40kHz.
[0016] Among them, 40kHz ultrasound breaks up the conductive carbon black agglomerates and works synergistically with sodium lignin sulfonate to avoid local interruption of the conductive path, which is beneficial to improving the uniformity of dispersion. Ethanol-assisted wetting and KH-550 coupling agent activation enhance the compatibility of the conductive filler with the starch matrix, reduce the resistivity, and are beneficial to strengthening the interface bonding.
[0017] Preferably, in step S1, the step of preparing the corn cross-linked oxidized starch adhesive comprises preparing corn cross-linked starch, then preparing corn cross-linked oxidized starch using the corn cross-linked starch as a raw material, and finally preparing the conductive adhesive using the corn cross-linked oxidized starch as a raw material;
[0018] Among them, the steps for preparing crosslinked corn starch include weighing 20 g of corn starch, adding 30 mL of distilled water to form a starch milk slurry, adding NaCl, placing it in a constant temperature water bath at 30-60 °C, stirring for 5 min, dropping 0.5-1.5 g of glutamic acid solution into the mixed solution, adjusting to a starch milk with a mass fraction of 10%, adding NaOH solution to adjust the pH of the starch milk to 6-11, maintaining stirring, reacting for 1.0-2.4 h. After the reaction is completed, adjust the pH to 6 with hydrochloric acid solution, let it stand, filter, wash with deionized water, and finally wash with absolute ethanol 2-3 times, perform suction filtration, place it in a drying oven, dry at 60 °C for 4 h, and pulverize through a 100-mesh sieve.
[0019] Among them, using corn starch as a raw material to replace petrochemical-based adhesives reduces the carbon footprint. The glutamic acid crosslinking agent and pH regulation optimize the three-dimensional network, which is beneficial to improving the water resistance and mechanical strength of the adhesive layer. The precise washing and drying process facilitate ensuring the product purity. After sieving, the particle size is uniform, which is conducive to subsequent coating.
[0020] Preferably, the steps for preparing crosslinked oxidized corn starch include weighing 20 g of crosslinked corn starch, adding distilled water to form a starch milk with a mass fraction of 30%, continuously stirring, adding FeSO4 solution, adding dilute hydrochloric acid solution to adjust the pH to 3, placing it in a constant temperature water bath at 50 °C, dropwise adding 2 mL of hydrogen peroxide solution, keeping the temperature at 50 °C, reacting for 3 h, adjusting the pH to 6-6.5 with NaOH solution, then adding sodium bisulfite solution, filtering, washing with deionized water until there is no chloride ion, washing with absolute ethanol 2-3 times, performing suction filtration, placing the product in a drying oven at 60 °C and drying for 4 h, and pulverizing through a 100-mesh sieve.
[0021] Hydrogen peroxide oxidation introduces polar groups (such as carboxyl groups), which is convenient for improving the affinity of the adhesive for the metal-coated base fabric. Oxidation enhances the adhesion force. FeSO4 accelerates the oxidation reaction, which is beneficial to shortening the process cycle. Sodium bisulfite terminates the reaction to avoid excessive degradation and maintains the integrity of the starch chain, which is convenient for optimizing the catalytic efficiency.
[0022] Preferably, the steps for preparing crosslinked oxidized corn starch adhesive include weighing crosslinked oxidized corn starch, preparing a suspension with a mass fraction of 12%, placing it in a constant temperature water bath at 95 °C and gelatinizing for 1 h, adding NaOH solution to adjust the pH of the system's regulating solution to 8-9, weighing 100 g of the mixed solution, adding 8-12 g of conductive carbon black, 0.8-1.2 g of sodium lignosulfonate, and 0.24 g of KH-550, stirring evenly, and taking it out and cooling to room temperature.
[0023] Among them, the 12% starch suspension forms appropriate rheological properties after gelatinization. The carbon black addition amount of 8-12% ensures that the conductive threshold is met and the coating is smooth, maintaining the balance between conductivity and viscosity. When the pH is 8-9, the colloid has high stability, which is convenient for preventing filler sedimentation. Sodium lignosulfonate further disperses carbon black, reduces the interfacial resistance, and stabilizes the system in an alkaline environment.
[0024] Preferably, in step S2, the plain conductive cloth includes a metal-coated layer on a polyester / cotton blended plain fabric.
[0025] Among them, the polyester / cotton blend provides mechanical strength and flexibility, and the metal coating (such as copper / nickel plating) imparts high surface conductivity. The plain weave structure ensures coating uniformity. In addition, the blended fabric is lighter in weight and more controllable in cost than pure metal foil, making it suitable for large-scale production.
[0026] Preferably, in step S3, an online thickness monitoring system is integrated in the knife coater, assisted by a laser thickness gauge, to provide real-time feedback for adjusting the knife pressure and controlling the thickness error within ±5μm.
[0027] The laser thickness gauge is convenient for providing real-time feedback and can dynamically adjust the knife pressure, controlling the thickness error within ±5μm, reducing material waste, improving product consistency, and the integrated monitoring system can avoid downtime for debugging, being suitable for continuous roll-to-roll manufacturing to facilitate high-speed production.
[0028] Preferably, in step S4, infrared drying assistance is introduced to quickly transfer heat inside the adhesive layer and shorten the total drying time to 12 minutes.
[0029] Infrared radiation directly heats the inside of the adhesive layer, avoiding the problems of surface hardening and internal moisture caused by traditional hot air drying. The total drying time is shortened to 12 minutes, which is beneficial to reducing energy consumption by more than 30%, improving the production line throughput, and saving energy and reducing consumption.
[0030] Preferably, in step S6, the lamination parameters are dynamically adjusted according to the thickness of the adhesive layer:
[0031] Among them, for an adhesive layer of 50-70μm, the pressure is 0.2-0.3MPa and the temperature is 80°C;
[0032] Among them, for an adhesive layer of 70-100μm, the pressure is 0.3-0.5MPa and the temperature is 100°C.
[0033] Differentiated treatment is carried out for different thicknesses, matching the pressure and temperature for different adhesive layer thicknesses. For example, low pressure for thin layers to prevent penetration and high pressure for thick layers to ensure bonding, avoiding insufficient lamination or substrate damage. And the temperature gradient control is beneficial to promoting the molecular-level bonding between the adhesive layer and the substrate, improving the peel strength and long-term durability.
[0034] Compared with the prior art, the preparation process of the present single-sided tape of plain conductive cloth has the following beneficial effects:
[0035] 1. The preparation process of the single-sided tape of plain conductive cloth provided by the present invention uses corn starch as the raw material, constructs a three-dimensional network structure adhesive through glutamic acid-mediated cross-linking reaction and oxidation modification, and systematically optimizes the key parameters by using the single-variable control experiment method.
[0036] 2. The preparation process of the single-sided tape of plain conductive cloth provided by the present invention explores the influence of different reaction temperatures on the sedimentation volume of corn cross-linked starch through single-factor experiments, and determines the optimal reaction temperature in the process parameters.
[0037] 3. The preparation process of the single-sided tape of plain conductive cloth provided by the present invention explores the influence of different glutamic acid addition amounts on the sedimentation volume of corn cross-linked starch through single-factor experiments, and determines the optimal addition amount of glutamic acid in the process parameters.
[0038] 4. The preparation process of the single-sided tape of plain conductive cloth provided by the present invention explores the influence of different pH values on the sedimentation volume of corn cross-linked starch through single-factor experiments, and determines the optimal reaction pH in the process parameters.
[0039] 5. The preparation process of the single-sided tape of plain conductive cloth provided by the present invention explores the influence of different reaction times on the sedimentation volume of corn cross-linked starch through single-factor experiments, and determines the optimal reaction time in the process parameters.
[0040] 6. The preparation process of the single-sided tape of plain conductive cloth provided by the present invention detects the basic physical and chemical properties of the adhesive to clarify the performance of the adhesive.
[0041] In summary, the present invention provides a preparation process of a single-sided tape of plain conductive cloth. Using corn starch as the raw material, a three-dimensional network structure adhesive is constructed through gradient oxidation cross-linking modification technology, and the conductive-bonding interface is optimized by coordinating conductive carbon black and silane coupling agent. Finally, it is compounded with a metal-coated polyester-cotton plain conductive cloth to make a high-performance tape, reducing carbon emissions during the production process, and the waste tape can achieve 90% biodegradation in the natural environment, fundamentally alleviating the pollution problem of persistent adhesives in electronic waste, and providing an innovative solution for green electronic manufacturing. Detailed Embodiments
[0042] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments. Specific Embodiment 1:
[0044] A preparation process of a single-sided tape of plain conductive cloth includes:
[0045] S1. Prepare a conductive adhesive. Prepare corn cross-linked oxidized starch adhesive according to the steps, add conductive carbon black, sodium lignin sulfonate, and silane coupling agent KH-550, and stir for 30 to 60 minutes to form a conductive adhesive;
[0046] S2. Pretreatment of plain conductive fabric: low-temperature plasma treatment of plain conductive fabric, power of 50-100W, treatment time of 2-5min, introduction of argon or oxygen mixed gas, ratio of 4:1;
[0047] S3, coating process, use a scraper coater or a roller coater to evenly coat the conductive adhesive on one side of the conductive fabric, and control the wet film thickness to 50-100 μm;
[0048] S4, staged drying, the first stage is drying at 40°C and 50% humidity for 5 minutes, the second stage is drying at 60°C and 30% humidity for 10 minutes to accelerate water evaporation;
[0049] S5, curing and molding, curing at 100-120°C for 20-30 minutes to completely cross-link the adhesive and form a stable conductive layer;
[0050] S6, pressing and slitting, using the pressing roller to ensure that the adhesive layer and the substrate are in close contact, and then slitting into rolls or sheets according to production requirements.
[0051] In terms of materials, a balance between environmentally friendly substrate and conductive performance is achieved through the combination of corn cross-linked oxidized starch adhesive and conductive carbon black. Adhesion is enhanced through pretreatment, and the surface of the conductive cloth is activated using low-temperature plasma treatment to improve the wettability of the adhesive and reduce the risk of delamination. In the subsequent segmented drying process, temperature and humidity are controlled in stages to avoid cracking of the adhesive layer, ensure drying uniformity, shorten process time, and promote complete cross-linking through high-temperature curing to form a stable conductive network and ensure long-term reliability.
[0052] In step S1, before stirring, conductive carbon black is mixed with sodium lignin sulfonate, KH-550 and a small amount of ethanol, and ultrasonically treated for 30 minutes;
[0053] Among them, the ultrasonic frequency is 40kHz.
[0054] Among them, 40kHz ultrasound breaks up the conductive carbon black agglomerates and works synergistically with sodium lignin sulfonate to avoid local interruption of the conductive path, which is beneficial to improving the uniformity of dispersion. Ethanol-assisted wetting and KH-550 coupling agent activation enhance the compatibility of the conductive filler with the starch matrix, reduce the resistivity, and are beneficial to strengthening the interface bonding.
[0055] In step S1, the steps of preparing the corn cross-linked oxidized starch adhesive include preparing corn cross-linked starch, then using the corn cross-linked starch as a raw material to prepare corn cross-linked oxidized starch, and finally using the corn cross-linked oxidized starch as a raw material to prepare the conductive adhesive;
[0056] Among them, the steps of preparing corn cross-linked starch include weighing 20 g of corn starch, adding 30 mL of distilled water to make a starch milk slurry, adding NaCl, placing it in a constant temperature water bath at 30 - 60 °C, stirring for 5 min, dropping 0.5 - 1.5 g of glutamic acid solution into the mixed solution, making a starch milk with a mass fraction of 10%, adding NaOH solution to adjust the pH of the starch milk to 6 - 11, keeping stirring, reacting for 1.0 - 2.4 h. After the reaction is completed, adjust the pH to 6 with hydrochloric acid solution, let it stand, filter, wash with deionized water, and finally wash with absolute ethanol 2 - 3 times, filter by suction, place it in a drying oven, dry at 60 °C for 4 h, and crush through a 100-mesh sieve.
[0057] Among them, using corn starch as a raw material to replace the petrochemical-based adhesive reduces the carbon footprint. The glutamic acid cross-linking agent and pH regulation optimize the three-dimensional network, which is beneficial to improving the water resistance and mechanical strength of the adhesive layer. The precise washing and drying process facilitate ensuring the product purity. After sieving, the particle size is uniform, which is conducive to subsequent coating.
[0058] The steps of preparing corn cross-linked oxidized starch include weighing 20 g of corn cross-linked starch, adding distilled water to make a starch milk with a mass fraction of 30%, stirring continuously, adding FeSO4 solution, adding dilute hydrochloric acid solution to adjust the pH to 3, placing it in a constant temperature water bath at 50 °C, dropping 2 mL of hydrogen peroxide solution drop by drop, keeping the temperature at 50 °C, reacting for 3 h, adjusting the pH to 6 - 6.5 with NaOH solution, then adding sodium bisulfite solution, filtering, washing with deionized water until there is no chloride ion, washing with absolute ethanol 2 - 3 times, filtering by suction, placing the product in a drying oven at 60 °C and drying for 4 h, and crushing through a 100-mesh sieve.
[0059] Hydrogen peroxide oxidation introduces polar groups (such as carboxyl groups), which is convenient for improving the affinity of the adhesive to the metal-coated base fabric. Oxidation enhances the adhesion force. FeSO4 accelerates the oxidation reaction, which is beneficial to shortening the process cycle. Sodium bisulfite terminates the reaction to avoid excessive degradation and maintains the integrity of the starch chain, which is convenient for optimizing the catalytic efficiency.
[0060] The steps of preparing the corn cross-linked oxidized starch adhesive include weighing the corn cross-linked oxidized starch, preparing a suspension with a mass fraction of 12%, placing it in a constant temperature water bath at 95 °C and gelatinizing for 1 h, adding NaOH solution to adjust the pH of the system to 8 - 9, weighing 100 g of the mixed solution, adding 8 - 12 g of conductive carbon black, 0.8 - 1.2 g of sodium lignosulfonate, and 0.24 g of KH-550, stirring evenly, and taking it out and cooling to room temperature.
[0061] Among them, the 12% starch suspension forms appropriate rheological properties after gelatinization. The carbon black addition amount of 8-12% ensures that the conductive threshold is met and the coating is smooth, maintaining the balance between conductivity and viscosity. When the pH is 8-9, the colloid has high stability, which is convenient for preventing the sedimentation of fillers. Sodium lignosulfonate further disperses carbon black, reduces the interfacial resistance, and stabilizes the system in an alkaline environment.
[0062] In step S2, the plain conductive cloth includes a metal-coated layer on a polyester / cotton blended plain fabric.
[0063] Among them, the polyester / cotton blend provides mechanical strength and flexibility, and the metal coating (such as copper / nickel plating) endows high surface conductivity. The plain weave structure ensures coating uniformity. In addition, the blended fabric is lighter and more cost-effective than pure metal foil, making it suitable for large-scale production.
[0064] In step S3, an online thickness monitoring system is integrated in the knife coater, assisted by a laser thickness gauge, to adjust the knife pressure in real-time feedback and control the thickness error to be less than ±5μm.
[0065] The laser thickness gauge is convenient for providing real-time feedback and can dynamically adjust the knife pressure, controlling the thickness error within ±5μm, reducing material waste, improving product consistency, and the integrated monitoring system can avoid downtime for debugging, being suitable for continuous roll-to-roll manufacturing to facilitate high-speed production.
[0066] In step S4, infrared drying assistance is introduced to rapidly transfer heat inside the adhesive layer and shorten the total drying time to 12 minutes.
[0067] Infrared radiation directly heats the inside of the adhesive layer, avoiding the problems of surface hardening and internal moisture caused by traditional hot air drying. The total drying time is shortened to 12 minutes, which is beneficial to reducing energy consumption by more than 30%, improving the throughput of the production line, and saving energy and reducing consumption.
[0068] In step S6, the lamination parameters are dynamically adjusted according to the thickness of the adhesive layer:
[0069] Among them, for an adhesive layer of 50-70μm, the pressure is 0.2-0.3MPa and the temperature is 80°C;
[0070] Among them, for an adhesive layer of 70-100μm, the pressure is 0.3-0.5MPa and the temperature is 100°C.
[0071] Differentiated treatment is carried out for different thicknesses, matching pressure and temperature for different adhesive layer thicknesses. For example, low pressure for thin layers to prevent penetration and high pressure for thick layers to ensure bonding, avoiding insufficient lamination or substrate damage. And the temperature gradient control is beneficial to promoting the molecular-level bonding between the adhesive layer and the substrate, improving the peel strength and long-term durability.
[0072] Specific example two:
[0073] Specific Example 2 is a screening test for the mixing temperature of the starch milk slurry mentioned in Specific Embodiment 1, to explore the influence law of solely changing the reaction temperature on the sedimentation volume of corn cross-linked starch. The content of Specific Example 2 is as follows:
[0074] 1. Preparation of corn cross-linked starch
[0075] Weigh 20 g of corn starch and place it in a reaction vessel. Add 180 mL of distilled water according to the solid-liquid ratio of 1:9 to prepare a starch milk slurry. Add NaCl, place it in a constant temperature water bath at 30 - 60 °C, stir for 5 min, slowly drip 0.9 g of glutamic acid solution into the mixed solution, add NaOH solution to adjust the pH of the starch milk to 9, keep stirring, react for 1.4 h. After the reaction is completed, adjust the pH to 6 with hydrochloric acid solution, let it stand, filter, wash three times with 200 mL of deionized water in sequence to remove soluble impurities, and finally wash 2 - 3 times with anhydrous ethanol, filter by suction, place it in a drying oven, dry at 60 °C for 4 h, crush and pass through a 100-mesh sieve to obtain the finished product of corn cross-linked starch with uniform particle size distribution.
[0076] 2. Sedimentation volume determination
[0077] Weigh 2.5 g of corn cross-linked starch with an electronic balance and place it in a 100-mL clean beaker. Accurately measure 47.50 mL of distilled water according to the solid-liquid ratio of 1:19 and inject it into the beaker. Use a magnetic stirrer to form a homogeneous starch emulsion. Place the beaker in a constant temperature water bath at 85 °C ± 0.5 °C, continue to stir for about 2 min, then remove the beaker from the water bath and cool it to room temperature. Then quantitatively transfer 10.00 mL of the starch emulsion to a 15-mL centrifuge tube with a calibrated 10-mL pipette. The centrifuge speed is set at 4000 r / min and the centrifugation time is set at 2 min. After centrifugation is completed, take out the centrifuge tube from the centrifuge, pour the clear liquid in the centrifuge tube into another identical centrifuge tube, record the volume of the supernatant (V), and calculate the corresponding sedimentation volume according to the following formula. Conduct 3 parallel determinations on the same sample. Calculate the sedimentation volume of corn cross-linked starch according to the following formula.
[0078] V C = 10 – V
[0079] In the formula: V C is the sedimentation volume, with the unit of mL; 10 is the fixed volume, with the unit of mL; V is the volume of the supernatant, with the unit of mL.
[0080] 3. Results
[0081] Table 1 Sedimentation volume table at different reaction temperatures
[0082]
[0083] Based on the significant linear negative correlation between the degree of crosslinking and sedimentation volume in the crosslinked starch system, the decrease in the sedimentation volume value can quantitatively characterize the increase in the intermolecular crosslinking density. The experimental data determination shows that when the reaction temperature rises to 55 °C, the sedimentation volume of the system reaches the minimum value, which is significantly lower than that of the control group at 30 °C, indicating that the starch molecular chains form the densest three-dimensional network structure through the glutamic acid crosslinking agent under this temperature condition. Therefore, this temperature is determined as the optimal crosslinking reaction condition and used as the benchmark parameter for subsequent functional modification. Specific Example 3:
[0085] Specific Example 3 is the screening test for the addition amount of glutamic acid mentioned in Specific Example 2, to explore the influence law of solely changing the addition amount of glutamic acid on the sedimentation volume of corn crosslinked starch. The content of Specific Example 3 is as follows:
[0086] 1. Preparation of corn crosslinked starch
[0087] Weigh 20 g of corn starch and place it in a reaction vessel. Add 180 mL of distilled water according to the solid-liquid ratio of 1:9 to prepare a starch slurry. Add NaCl, place it in a constant temperature water bath at 55 °C, stir for 5 min, slowly drip 0.5 - 1.5 g of glutamic acid solution into the mixed solution, add NaOH solution to adjust the pH of the starch slurry to 9, keep stirring, react for 1.4 h. After the reaction is completed, adjust the pH to 6 with hydrochloric acid solution, let it stand, filter, wash it three times with 200 mL of deionized water in sequence to remove soluble impurities, and finally wash it 2 - 3 times with absolute ethanol, filter by suction, place it in a drying oven, dry it at 60 °C for 4 h, crush it through a 100-mesh sieve to obtain the finished product of corn crosslinked starch with uniform particle size distribution.
[0088] 2. Determination of sedimentation volume
[0089] Weigh 2.5 g of corn crosslinked starch with an electronic balance and place it in a 100 mL clean beaker. Accurately measure 47.50 mL of distilled water according to the solid-liquid ratio of 1:19 and inject it into the beaker. Use a magnetic stirrer to form a homogeneous starch emulsion. Place the beaker in a constant temperature water bath at 85 °C ± 0.5 °C, continuously stir for about 2 min, then remove the beaker from the water bath and cool it to room temperature. Then quantitatively transfer 10.00 mL of the starch emulsion to a 15 mL centrifuge tube with a calibrated 10 mL pipette. The centrifuge speed is set at 4000 r / min and the centrifugation time is set at 2 min. After centrifugation is completed, take out the centrifuge tube from the centrifuge, pour the clear liquid in the centrifuge tube into another centrifuge tube of the same type, record the volume of the supernatant (V), and calculate the corresponding sedimentation volume according to the following formula. Conduct 3 parallel determinations on the same sample. Calculate the sedimentation volume of corn crosslinked starch according to the following formula.
[0090] V C = 10 – V
[0091] Where: V CThe sedimentation volume is in mL; 10 is the fixed volume in mL; V is the supernatant volume in mL.
[0092] 3. Results
[0093] Table 2 Sedimentation volume table at different glutamic acid addition amounts
[0094]
[0095] It can be seen from the table that when the glutamic acid addition amount increases to 0.9 g, the sedimentation volume of the system reaches the lowest value, indicating that at this dosage, glutamic acid molecules promote the formation of a dense cross-linked network with the smallest steric hindrance in the starch molecular chain through amide bond / ester bond bridging. Based on this, 0.9 g of glutamic acid is selected as the optimal dosage of the cross-linking agent, and subsequent tests are carried out. Specific Example 4:
[0097] Specific Example 4 is a pH screening test mentioned in Specific Example 3 to explore the influence law of single pH change on the sedimentation volume of corn cross-linked starch. The content of Specific Example 4 is as follows:
[0098] 1. Preparation of corn cross-linked starch
[0099] Weigh 20 g of corn starch and place it in a reaction vessel. Add 180 mL of distilled water according to the solid-liquid ratio of 1:9 to prepare a starch milk slurry. Add NaCl, place it in a constant temperature water bath at 55 °C, stir for 5 min, slowly drop 0.9 g of glutamic acid solution into the mixed solution, add NaOH solution to adjust the pH of the starch milk to 6 - 11, keep stirring, react for 1.4 h. After the reaction is completed, adjust the pH to 6 with hydrochloric acid solution, let it stand, filter, wash three times with 200 mL of deionized water in turn to remove soluble impurities, and finally wash 2 - 3 times with absolute ethanol, filter by suction, place it in a drying oven, dry at 60 °C for 4 h, and crush through a 100-mesh sieve to obtain a finished product of corn cross-linked starch with uniform particle size distribution.
[0100] 2. Sedimentation volume measurement
[0101] Weigh 2.5 g of corn cross-linked starch using an electronic balance and place it in a clean 100 mL beaker. Accurately measure 47.50 mL of distilled water according to a solid-liquid ratio of 1:19 and pour it into the beaker. Use a magnetic stirrer to form a homogeneous starch emulsion. Place the beaker in a constant temperature water bath at 85 °C ± 0.5 °C. After continuously stirring for about 2 minutes, remove the beaker from the water bath and cool it to room temperature. Then, quantitatively pipette 10.00 mL of the starch emulsion into a 15 mL centrifuge tube using a calibrated 10 mL pipette. Set the centrifuge speed to 4000 r / min and the centrifugation time to 2 minutes. After centrifugation is complete, take out the centrifuge tube from the centrifuge, pour the clear liquid in the centrifuge tube into another identical centrifuge tube, record the volume of the supernatant (V), and calculate the corresponding sedimentation volume according to the following formula. Conduct 3 parallel determinations on the same sample. Calculate the sedimentation volume of the corn cross-linked starch according to the following formula.
[0102] V C = 10 – V
[0103] In the formula: V C is the sedimentation volume, with the unit of mL; 10 is the fixed volume, with the unit of mL; V is the volume of the supernatant, with the unit of mL.
[0104] 3. Results
[0105] Table 3 Sedimentation volume table at different pH values
[0106]
[0107] It can be seen from the table that when the reaction system is in the pH range of 6.0 - 9.0, as the pH increases, the sedimentation volume of the corn cross-linked starch gradually decreases. When pH > 9, as the pH increases, the sedimentation volume of the corn cross-linked starch also increases. Therefore, pH = 9 is selected for subsequent experiments. Specific Example Five:
[0109] Specific Example Five is the screening test of the reaction time mentioned in Specific Example Four, to explore the influence law of solely changing the reaction time on the sedimentation volume of corn cross-linked starch. The content of Specific Example Five is as follows:
[0110] 1. Preparation of corn cross-linked starch
[0111] Weigh 20 g of corn starch and place it in a reaction vessel. Add 180 mL of distilled water according to a solid-liquid ratio of 1:9 to prepare a starch slurry. Add NaCl, place it in a constant temperature water bath at 55 °C, stir for 5 min, slowly add 0.9 g of glutamic acid solution to the mixed solution, add NaOH solution to adjust the pH of the starch slurry to 9, keep stirring, and react for 1.0 - 2.4 h. After the reaction is completed, adjust the pH to 6 with hydrochloric acid solution, let it stand, filter, wash it three times with 200 mL of deionized water in sequence to remove soluble impurities, and finally wash it 2 - 3 times with absolute ethanol, filter by suction, place it in a drying oven, dry it at 60 °C for 4 h, pulverize it through a 100-mesh sieve to obtain a finished product of corn cross-linked starch with uniform particle size distribution.
[0112] 2. Determination of sedimentation volume
[0113] Weigh 2.5 g of corn cross-linked starch with an electronic balance and place it in a 100 mL clean beaker. Accurately measure 47.50 mL of distilled water according to a solid-liquid ratio of 1:19 and pour it into the beaker. Use a magnetic stirrer to form a homogeneous starch emulsion. Place the beaker in a constant temperature water bath at 85 °C ± 0.5 °C, continuously stir for about 2 min, then remove the beaker from the water bath and cool it to room temperature. Then, quantitatively transfer 10.00 mL of the starch emulsion to a 15 mL centrifuge tube with a calibrated 10 mL pipette. Set the centrifuge speed to 4000 r / min and the centrifugation time to 2 min. After centrifugation is completed, take out the centrifuge tube from the centrifuge, pour the clear liquid in the centrifuge tube into another identical centrifuge tube, record the volume of the supernatant (V), and calculate the corresponding sedimentation volume according to the following formula. Conduct 3 parallel determinations on the same sample. Calculate the sedimentation volume of corn cross-linked starch according to the following formula.
[0114] V C = 10 – V
[0115] In the formula: V C is the sedimentation volume, with the unit of mL; 10 is the fixed volume, with the unit of mL; V is the volume of the supernatant, with the unit of mL.
[0116] 3. Results
[0117] Table 4 Sedimentation volume table at different reaction times
[0118]
[0119] It can be seen from the table that when the reaction time is extended to 1.4 h, the sedimentation volume of the system reaches the lowest value. When the reaction time exceeds 1.4 h, the sedimentation volume shows an upward trend. Based on this, the reaction time of 1.4 h is selected as the optimal reaction time for subsequent experiments. Specific Example Six:
[0121] Specific Example 6 is the basic physical and chemical property detection test of the adhesives mentioned in Specific Embodiments 1 to 5. The content of Specific Example 6 is as follows:
[0122] 1. Preparation of the adhesive
[0123] Weigh 20 g of corn starch and place it in a reaction vessel. Add 180 mL of distilled water according to the solid-liquid ratio of 1:9 to prepare a starch milk slurry. Add NaCl and place it in a constant temperature water bath at 55 °C. Stir for 5 min. Slowly add 0.9 g of glutamic acid solution to the mixed solution. Add NaOH solution to adjust the pH of the starch milk to 9. Keep stirring and react for 1.4 h. After the reaction is completed, adjust the pH to 6 with hydrochloric acid solution, let it stand, filter, wash three times with 200 mL of deionized water in sequence to remove soluble impurities, and finally wash 2 - 3 times with absolute ethanol, filter by suction, place it in a drying oven, dry at 60 °C for 4 h, pulverize and pass through a 100-mesh sieve to obtain a finished product of corn cross-linked starch with uniform particle size distribution. Weigh 20 g of the finished product of corn cross-linked starch, add distilled water, and adjust it to a starch milk with a mass fraction of 30%. Keep stirring, add FeSO4 solution, add dilute hydrochloric acid solution to adjust the pH to 3, place it in a constant temperature water bath at 50 °C, gradually add 2 mL of hydrogen peroxide solution, keep the temperature at 50 °C, react for 3 h, adjust the pH to 6 - 6.5 with NaOH solution, then add sodium bisulfite solution, filter, wash with deionized water until there is no chloride ion, wash 2 - 3 times with absolute ethanol, filter by suction, place the product in a drying oven at 60 °C and dry for 4 h, pulverize and pass through a 100-mesh sieve. Weigh the corn cross-linked oxidized starch, prepare a suspension with a mass fraction of 12%, place it in a constant temperature water bath at 95 °C and gelatinize for 1 h. Add NaOH solution to adjust the pH of the system to 8 - 9. Weigh 100 g of the mixed solution, add 8 - 12 g of conductive carbon black, 0.8 - 1.2 g of sodium lignosulfonate, and 0.24 g of KH-550. Stir evenly and take it out to cool to room temperature.
[0124] 2. Detection of physical and chemical data
[0125] pH: Measure the pH using a pHS-3C digital precision pH meter in a constant temperature water bath at a temperature of (25 ± 1) °C.
[0126] Appearance: Observe the appearance with the eyes under natural light or daylight.
[0127] Viscosity: Measure the viscosity using an NDJ-8S digital viscometer in a constant temperature water bath at a temperature of (23 ± 1) °C.
[0128] Solid content: Put the sample into a constant temperature forced-air drying oven, dry at (120 ± 1) °C for (120 ± 1) min, take it out and weigh immediately with a precision of 0.001 g.
[0129] Storage stability: Accurately weigh 10.0 g and 400.0 g of the sample, place them in a test tube and a conical flask respectively, and perform constant temperature treatment in a constant temperature water bath at (70±2)°C (the liquid level of the sample is 20 mm below the liquid level of the water bath). Observe the fluidity of the test tube every hour since sealing, and cool the sample in the conical flask to 25°C to measure the viscosity, and calculate the viscosity change rate. When the viscosity growth rate reaches 200%, terminate the test, record the time t (h), and the storage stability is expressed as t×10 (that is, the number of days of storage in the dark and sealed at 10-20°C is 10t).
[0130] 3. Results
[0131] Table 5 Basic physical and chemical properties table
[0132]
[0133] It can be seen from the table that the corn cross-linked oxidized starch adhesive prepared from corn cross-linked starch after oxidation treatment exhibits good fluidity and storage stability.
[0134] Conclusion: The optimal process parameters for preparing corn cross-linked starch are determined from the above results as follows: a constant temperature water bath at 55°C, the addition amount of glutamic acid solution is 0.9 g, the pH of the starch milk is adjusted to 9 by adding NaOH solution, and the reaction time is 1.4 h. Prepare the corn cross-linked oxidized starch adhesive with these process parameters and combine it with conductive cloth to prepare the tape.
[0135] The specific embodiments described in this article are only illustrative of the spirit of the present invention. Those skilled in the art to which the present invention pertains can make various modifications or supplements to the described specific embodiments or use similar methods to replace them, but will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A preparation process of a plain conductive cloth single-sided tape, characterized in that, include: S1. Prepare a conductive adhesive. Prepare corn cross-linked oxidized starch adhesive according to the steps, add conductive carbon black, sodium lignin sulfonate, and silane coupling agent KH-550, and stir for 30 to 60 minutes to form a conductive adhesive; S2. Pretreatment of plain conductive fabric: low-temperature plasma treatment of plain conductive fabric, power of 50-100W, treatment time of 2-5min, introduction of argon or oxygen mixed gas, ratio of 4:1; S3, coating process, use a scraper coater or a roller coater to evenly coat the conductive adhesive on one side of the conductive fabric, and control the wet film thickness to 50-100 μm; S4, staged drying, the first stage is drying at 40°C and 50% humidity for 5 minutes, the second stage is drying at 60°C and 30% humidity for 10 minutes to accelerate water evaporation; S5, curing and molding, curing at 100-120°C for 20-30 minutes to completely cross-link the adhesive and form a stable conductive layer; S6, pressing and slitting, using the pressing roller to ensure that the adhesive layer and the substrate are in close contact, and then slitting into rolls or sheets according to production requirements.
2. The preparation process of a plain conductive fabric single-sided tape as described in claim 1, characterized in that, In step S1, before stirring, conductive carbon black is mixed with sodium lignin sulfonate, KH-550 and a small amount of ethanol, and ultrasonically treated for 30 minutes; Among them, the ultrasonic frequency is 40kHz.
3. The preparation process of a plain conductive fabric single-sided tape as described in claim 1, characterized in that, In step S1, the step of preparing corn cross-linked oxidized starch adhesive includes preparing corn cross-linked starch, then preparing corn cross-linked oxidized starch using the corn cross-linked starch as a raw material, and finally preparing a conductive adhesive using the corn cross-linked oxidized starch as a raw material; The steps of preparing corn cross-linked starch include weighing 20g corn starch, adding 30mL distilled water to make starch slurry, adding NaCl, placing in a constant temperature water bath at 30-60°C, stirring for 5min, dropping 0.5-1.5g glutamic acid solution into the mixed solution to make starch slurry with a mass fraction of 10%, adding NaOH solution to adjust the pH of the starch slurry to 6-11, keeping stirring, reacting for 1.0-2.4h, and after the reaction is completed, adjusting the pH to 6 with hydrochloric acid solution, standing, filtering, washing with deionized water, and finally washing with anhydrous ethanol for 2-3 times, filtering, placing in a drying oven, drying at 60°C for 4h, and crushing through a 100-mesh sieve.
4. The preparation process of a plain conductive fabric single-sided tape as described in claim 3, characterized in that, The steps of preparing corn cross-linked oxidized starch include weighing 20g corn cross-linked starch, adding distilled water to adjust to a starch milk with a mass fraction of 30%, stirring continuously, adding FeSO4 solution, adding dilute hydrochloric acid solution to adjust the pH to 3, placing in a 50°C constant temperature water bath, adding 2mL hydrogen peroxide solution dropwise, keeping the temperature at 50°C, reacting for 3h, adjusting the pH to 6-6.5 with NaOH solution, adding sodium bisulfite solution, filtering, washing with deionized water until there is no chloride ion, washing with anhydrous ethanol for 2-3 times, filtering by suction, placing the product in a drying oven at 60°C for 4h, and crushing it through a 100-mesh sieve.
5. The preparation process of a plain conductive fabric single-sided tape according to claim 4, characterized in that, The steps for preparing the corn crosslinked oxidized starch adhesive include weighing the corn crosslinked oxidized starch, preparing a suspension with a mass fraction of 12%, pasting it in a constant temperature water bath at 95 °C for 1 h, adding a NaOH solution to adjust the pH of the system to 8-9, weighing 100 g of the mixed solution, adding 8-12 g of conductive carbon black, 0.8-1.2 g of sodium lignosulfonate, and 0.24 g of KH-550, stirring evenly, and taking it out to cool to room temperature.
6. The preparation process of a plain conductive fabric single-sided tape as described in claim 1, characterized in that, In step S2, the plain conductive fabric includes a polyester / cotton blended plain fabric plated with a metal layer.
7. The preparation process of a plain conductive fabric single-sided tape as described in claim 1, characterized in that, In step S3, an on-line thickness monitoring system is integrated in the knife coater, assisted by a laser thickness gauge, and the knife pressure is adjusted in real-time feedback to control the thickness error to be less than ±5 μm.
8. The preparation process of a plain conductive cloth single-sided tape as described in claim 1, characterized in that, In step S4, infrared drying assistance is introduced to rapidly transfer heat inside the adhesive layer, shortening the total drying time to 12 minutes.
9. The preparation process of a plain conductive cloth single-sided tape as described in claim 1, characterized in that, In step S6, the pressing parameters are dynamically adjusted according to the adhesive layer thickness: Among them, for an adhesive layer of 50-70 μm, the pressure is 0.2-0.3 MPa and the temperature is 80 °C; Among them, for an adhesive layer of 70-100 μm, the pressure is 0.3-0.5 MPa and the temperature is 100 °C.
Citation Information
Patent Citations
Elastic conductive colloid, preparation method and application thereof
CN104558699A
High-viscidity electroconductive foam backing adhesive and preparation process thereof
CN110643297A
Environment-friendly sealing binder for corrugated paper and preparation method of environment-friendly sealing binder
CN117844400A
Tape for preventing static electricity
KR1020080068514A
Cited By
Adhesive curing detection method, device and equipment and storage medium
CN120847187A